THE POSITION OF SEPARATE CREDITOR HOLDERS OF THIRD-PARTY COLLATERAL IN EXECUTING COLLATERAL OBJECTS DURING INSOLVENCY - Moh. Harish Mubrizul Haq; Budi Parmono; Rahmatul Hidayati (International Journal of Cultural and Social Science, 2025)
This research aims to analyze the legal position of preferential creditors regarding collateral owned by third parties (guarantor) within the bankruptcy system in Indonesia, using a normative juridical approach and case studies of commercial court rulings. In practice, there is often inconsistency between legal norms and their application, especially when the curator includes third-party collateral in the bankruptcy estate without a valid legal basis. Based on Articles 55 and 56 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU), a separatis creditor has an execution right that can still be carried out independently, even if the debtor is declared bankrupt. These rights are protected by the principles of droit de préférence, droit de suite, and the accessory principle in the theory of property security. This research also shows that the curator does not have the legal authority to determine the ownership status of the collateral object, which should be determined by the court. Protection of third-party property rights is guaranteed by the theory of property protection and the constitution. Therefore, consistency in the application of law, technical guidelines, and stable jurisprudence is necessary to ensure legal certainty, justice, and balanced protection of the rights of all parties in the bankruptcy process.